Earnings Management via Not-Wholly-Owned Subsidiaries - Luo, Mei; Zhang, Frank; Zhang, Xinyi (Management Science, 2024)
We investigate an unexplored mechanism of earnings management: income shifting from not-wholly-owned subsidiaries to help the parent company avoid losses at the expense of subsidiaries. Consolidated net income attributable to the parent company (i.e., net income) increases through this mechanism, as the parent company enjoys the full amount of the shifted earnings rather than sharing them with minority investors. We design an empirical model to directly estimate the amount of income shifted from subsidiaries to parent firms. Employing this measure, we find that firms opportunistically decrease earnings of their not-wholly-owned subsidiaries to manage net income upward to avoid losses. The results are stronger for firms with high noncontrolling ownership, firms with large subsidiaries, firms with strong influence over not-wholly-owned subsidiaries, and firms with a high level of related-party transactions. Our results are robust to alternative research designs, including controls for within-firm variations, alternative earnings thresholds, propensity score matching, and entropy balancing techniques. Our mechanism of earnings management is generalizable to other earnings management scenarios, such as share pledging. This paper was accepted by Brian Bushee, accounting. Funding: X. Zhang thanks the National Natural Science Foundation of China [Grant 72102243] for financial support. M. Luo thank the financial support from National Natural Science Foundation of China [Grant 71840011], and the Research Center for Digital Financial Assets at School of Economics and Management of Tsinghua University. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.03090 .